2013
DOI: 10.4081/gh.2013.96
|View full text |Cite
|
Sign up to set email alerts
|

Socio-environmental variables and transmission risk of lymphatic filariasis in central and northern Mozambique

Abstract: Abstract. Lymphatic filariasis (LF) is endemic in Mozambique, where it is caused by Wuchereria bancrofti with Culex quinquefasciatus as the main vector. It affects approximately 10% of the population (2 million) with about 16 million at risk. Prevalence rates in 40 out of 65 districts that together comprise the four endemic provinces Niassa, Cabo Delgado, Nampula and Zambezia were analysed with the aim of elucidating the socio-environmental variables influencing the transmission. The levels of prevalence were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Some villages depicted low prevalence of CFA, which might be due to various interventions creating synergy besides the MDA, such as the use of insecticide-treated nets or local insecticide repellants (smoke, herbs), as observed in studies conducted elsewhere [34]. In some cases, the presence of climatic and environmental conditions that are unfavorable for vector survival could contribute to low infection or positivity rates, even in areas where compliance to MDA is low [35]. However, this study did not explore the entomological characteristics and, therefore, no link could be established in this case, albeit other studies had reported similar conclusions [36].…”
Section: Discussionmentioning
confidence: 99%
“…Some villages depicted low prevalence of CFA, which might be due to various interventions creating synergy besides the MDA, such as the use of insecticide-treated nets or local insecticide repellants (smoke, herbs), as observed in studies conducted elsewhere [34]. In some cases, the presence of climatic and environmental conditions that are unfavorable for vector survival could contribute to low infection or positivity rates, even in areas where compliance to MDA is low [35]. However, this study did not explore the entomological characteristics and, therefore, no link could be established in this case, albeit other studies had reported similar conclusions [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, except for results from recent field surveys in Malawi [2-4] and a socio-environmental study on transmission risk in northern Mozambique [5], knowledge on LF infection, disease and transmission patterns in the central and southern region of Africa is limited. Available information from case reports and historic surveys indicate, though, that LF has a wider distribution in this part of Africa [6-9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was a lower frequency of cases in people < 15 years old [53]. In 2009, Mozambique was still one of the 39 African countries that are endemic for LF, with 16 million people estimated at risk and two million infected; Cabo Delgado and Nampula were the provinces with higher risk [54].…”
Section: Resultsmentioning
confidence: 99%